Improving Students’ Speaking Ability through Digital Game-Based Learning in the Era of Society 5.0 at Ninth Graders Students of MTs N 02 Rensing - Safari, M.Ubaidillah Karomi (Universitas Pahlawan Tuanku Tambusai, 2025)
Islamic boarding schools have a strategic role in instilling basic knowledge based on Islam, so that students can face the era of societal transformation towards a modern future. The objectives of this study were: (1) To improve the students’ speaking ability through Quizizz as digital game-based learning. 2) To improve students’ learning motivation through Quizizz as digital game-based learning. This study employs classroom action research (CAR) to systematically improve students’ speaking ability. I used the speaking test as an instrument. The data analysis is used individually and classically. Based on the data findings of each cycle’s activities. I come up to point to be drawn that teaching English for speaking skill for the ninth graders of students through Quizizz as digital game-based learning could improve students’ speaking ability. The improving percentage of students achieving passing grade gained 71.69% in the first cycle and improved to 78.35 % in the second cycle.